Pobreza objetiva e subjetiva no Brasil - Alexandre Gori Maia; Antonio Marcio Buainain (Confins)
This paper analyzes poverty in Brazil, measured by objective indicator of per capita income and subjective indicators of income and food insufficiency. Analyses highlight spatial differences, both differences between States and differences between urban and rural areas. Analyses are based on results of the Brazilian Pesquisa de Orçamentos Familiares (POF) 2002/2003 and 2008/2009. Overall, results show a substantial reduction of the level of poverty in Brazil, specially for those related to more severe conditions of income and food insufficiency and in the more vulnerable regions. Analyses also suggest that people with similar income are more likely to declare income and food sufficiency in rural areas, although the percent of insufficiency is higher in the rural areas.